Traceability of Distribution Processes through the Application of IoT and Big Data in Logistics Companies in Mexico - Serrano-Guzmán, María Julieta (2026)
This study analyzes how Industry 4.0 technologies—particularly IoT and Big Data—can enhance traceability in the distribution stage of imported raw materials, specifically steel and silica sand, for a logistics company located in Mexico. In the context of international trade and global supply chains, logistics and traceability are critical for maintaining competitiveness, especially in Mexico, where the logistics sector accounts for 5.5% of GDP. A qualitative methodology was employed, including a case study, literature review, and semi-structured interviews with experts in logistics and Industry 4.0. The findings indicate that IoT and Big Data enable real-time visibility, predictive analytics, and improved coordination among supply chain actors; however, their adoption faces technological, organizational, and investment-related barriers. The study proposes digital strategies to optimize processes and ensure operational continuity in the Mexican firm. It concludes that IoT and Big Data not only optimize logistics processes but also enhance continuity, transparency, and competitiveness for organizations.